IMPLEMENTATION OF BUILDING INFORMATION MODELING ON SLOPE STABILITY AND MITIGATION ANALYSIS IN ACEH, INDONESIA - Purnama, Adhitya Yoga; Latif, Devi Okatviana; Kurniawan, Aswin Wahyu; Adriyati, Meilani (Journal of Applied Engineering Science, 2022)
Slope failure in the well site area in Aceh, Indonesia caused the termination of gas distribution and resulted in financial loss. Based on the visual observation, the slope failed due to the high intensity of rainfall, which influenced the reduction of soil shear strength of the slope embankment. Moreover, the slope reinforcement has been damaged due to the collapsed trees on the slope embankment. Slope stability analysis was carried out by using a two-dimensional (2D) numerical method in several section areas to determine the appropriate slope reinforcement or countermeasures. Based on the 2D slope stability analysis, the Building Information Modeling (BIM) was performed by using a 3D projection drawing to evaluate the detailed information of the area which was applied by the countermeasures system. This method describes the total area and material quantity covered by the countermeasure system to determine the information material quantity and land acquisition area. Furthermore, the implementation of BIM in this study provides detailed information during the construction process to ensure comprehensive landslide mitigation.